Apakah Kreativitas dan Sikap terhadap Ilmu Ekonomi Meramalkan Partisipasi Politik Mahasiswa? Peran Mediasi Efikasi Politik pada Mahasiswa di Malang, Jawa Timur - Abraham, Juneman; Viatre, Diantini Ida (UI Scholars Hub, 2013)
This research aims to find the psychological mechanism of students’ political participation. The research was designed with predictive correlational design and the data analysis technique was path analysis. The dependent variable was political participation intention. The predictor variables were creativity and students’ attitude toward economics. The mediator variables were the necessary political experience and political efficacy. One hundred and four students of Department of Psychology, FPPsi, Malang State University, participated (Mage = 19.50 years old; SDage = 2.397 years). The research found that creativity and attitude toward economics are significant predictors for students’ political participation intention and this prediction is mediated by political efficacy and the necessary political experience (Chi-Square = 8.24, df = 5, P-value = 0.14349, GFI = 0.97, RMSEA = 0.08).